Analisa Dan Perancangan Cylinder Block Mesin Compressor Tipe SDP 07-25 ¾ HP 25L - Ricky Fernandez; Menhendry Menhendry; Yuliarman Yuliarman (Politeknik Negeri Padang, 2018)
A compressor is a mechanical device used to increase fluid pressure, both gas and air pressure. The most used compressors are SDP 07-25 ¾ HP 25L compressors. Then Cylinder Block is a component inside the compressor that functions as the place where the piston and ring work to take place to do the work process, suction, compression and exhaust. The emergence of the idea of the process of reproducing Cylinder Block is so that an organization or company is able to produce independently of the Cylinder Block and to minimize costs in the production process. The most basic thing that is done for this process of reproduction / reverse engineering is by doing Machining techniques. Machining technique is the production process of a component in an easy way